Desenvolvimento de um sistema de climatização híbrido: dessecante e por compressão de vapor - Melo, Francisco José Araujo (2019)
In the present work, a hybrid artificial air conditioning system was developed on the basis of the technologies of desiccant air conditioning and air conditioning by steam compression (CCV). Its structure was divided into two stages, the first to reduce the latent loads of the air conditioning by means of the dehumidification process in adsorption wheels, and the second to reduce the sensitive loads of the air conditioning by means of heat transfer in a rotary heat exchanger and a compact heat exchanger. The adsorption wheels used were a desiccant wheel (RD) and an enthalpy wheel (RE), the rotary heat exchanger was a regenerative heat exchanger type (sensible wheel), and the compact heat exchanger was the evaporator constituting a residential CCV window system. The enthalpy wheel was inserted into the system to act in conjunction with the desiccant wheel and was presented as an excellent means to achieve higher levels of dehumidification and also reductions in the consumption of the heat source used to reactivate the adsorbent of the desiccant wheel. As a way of further reducing the consumption of the heat source, the thermal residues dissipated from the constituent condenser of the CCV system were used. The hybrid system in open ventilation mode was evaluated from two test blocks, the first one using airflows of 909 m³/h, and the second using flow rates of 1204 m³/h. The performances, Thermal (), Electrical () and General () were observed. Reactivation temperatures maintained at around 50, 65 and 80℃ were used in each test block. In the test block with flow rates of 909 m³ / h, the maximum performance coefficients were βT_52.0°C= 2.2, βE_80.5°C= 3.4, βG_52.0°C= 0.9. In the test block with flow rates of 1204 m³/h, the maximum performance coefficients were βT_49.8°C= 2.5, βE_80.1°C= 4.2, βG_49.8°C= 1.1. From the case studies, the RD performance was compared with the performance of the set, RD + RE. It was observed in the flows of 909 and 1204 m³/h, that by means of the joint action of the rotors, reductions of the consumption of the heat source of 57.6% and 61.8%, respectively, were obtained. In each test block it was also observed that, in the lower reactivation temperature, the joint performance of the rotors promoted dehumidification levels equivalent to those achieved by the RD reactivated with the higher established temperature. Due to the use of the thermal residues dissipated in the condenser, in the test block with flow rates of 909 m³/h and reactivation temperatures of 52.0℃, 65.9℃ and 80.5℃, the heat source consumption was saved in 100% 71.9% and 51.1%, respectively. Similarly, in the test block with flow rates of 1204 m³/h and with reactivation temperatures of 49.8℃, 66.0℃ and 80.1℃, the consumption of the heat source was saved in 100%, 71.8% and 52.5%, respectively.